Analisis Perbedaan Abnormal Return Saham LQ45 Diseputar Peristiwa Pergantian Pemerintahan Baru Di Indonesia: Studi Kasus Saham LQ45 Periode Agustus 2004-Februari 2005 di Bursa Efek Jakarta - Yusnaidy Tenggara; Astuti Setyani (Jurnal Riset Manajemen dan Bisnis, 2006)
One important objective of investor's short term investment on stockmarket is to obtoin the positive stock abnormal return. In this cose, theexistence of such return will be determined by both the external factors andinternal factors. Studies on Indonesio's stock market shows, the externalfactors qre more influential than those the internal one. On that case, the twoimportant external factors ore primarily political and economic condition,since they are correlated each others. Political and economic stability is veryimportant to mointain a secure and safe investment climate on the stockmarket.This research however, will be focused on political issue to examine itseffect on stock abnormol return especially the issue surround the Indonesia'sgovernment succession in the perio,d of August 2004 until February 2005.Using the method of event study, this research is done on LQ45 stock. Itis also employ the cluster sampling method to define the sample and resultedon 45 stock which was issued on August 2A04 until February 2005. Then thestoclrs are calculated by their actual return, market return, abnormal return,average abnormal return, cumulative averoge abnormal return, and estimatedstandard etror. Finally, this research use Paired Sample T-test to examine thehypothesis. The results shows there are significantly no differences betweenLQ45's stock abnormal return before and after the governmental powerchonges.Keywords: Indonesia new government and stock return.